Peoples’ choices and behaviour in urban streets / Norhafizah Abdul Rahman, Shuhana Shamsuddin and Tim Heath - Abdul Rahman, Norhafizah; Shamsuddin, Shuhana; Heath, Tim (2012)
The street is a vital part of the public space in urban areas that cater for users’ functional, social and leisure needs. Currently, in Malaysia there has been a growing concern towards promoting streets that are friendly to all users. This is because there are not many examples of street environments that are friendly and accommodating to the users. Based on previous research, people are more ready to walk than today in the case of improved public spaces. In order to ensure the successful design of urban street, the understanding of street’s characteristics and qualities and users’ activities on the street are important. The research examines the concept of ‘user-friendly street’ in the context of Malaysian town centre. The primary concern of the research is to study the needs of the users that contribute to the use of streets and their livability in the urban areas of Malaysia. There are two complementary research methods used in this research, namely field study and survey. A single case study was applied in this study. The case study chosen is one of the main shopping streets in Kuala Lumpur and is selected based on the physical, functional and socio cultural characteristics of the street. The inventory of the case study is based on field observations of activities using schedule checklists, photographs and maps procedures. In this research, users’ perceptions element was obtained through a sample survey of daily users, occasional users and non-users. The research has found that there are variations in the users’ perception towards the factors and attributes that contribute to user-friendly street between different types of users and socio backgrounds. The streets were not only used by the users based on physical and functional qualities but also based on the meaning. It is expected that the findings will improve our understanding of what we consider to be the public realm in terms of the physical characteristics and qualities that support the user’s friendly built environments. This will help the designers, urban planners and policy makers to understand the needs and attitudes of users towards the concept of a user-friendly street in Malaysia.